Latency measurement of 100 km fiber using correlation-OTDR - Azendorf, Florian; Dochhan, Annika; Schmauß, Bernhard; Eiselt, Michael (Photonische Netze - 20. ITG-Fachtagung, 2020)
By means of C-OTDR (Correlation - Optical Time Domain Reflectometry), we measured the latency of 100 km fiber with an accuracy of a few picoseconds. Based on iterating 49 measurements, we calculated a standard deviation of 12 ps between the round-trip latency values. To verify the reflection measurements, we used a single pass setup without reflector, which showed a maximum difference of only 11 ps.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Fiber characterization; Latency; Optical Time Domain Reflectometry; Propagation delay